Pengembangan Model Pemberdayaan Petani Padi melalui Program Hulu Hilir Agromaritim Bidang Pertanian - Khusna, Khanifatul; Kurniati, Ruri Fadhilah; Muhaimin, Mohammad (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2019)
The purpose of this study is to explore and describe the model of empowerment of rice farmers by the local government as a function of empowerment. Rice farmers are the subject of research due to their position as the largest producer of food crops in Indonesia, even in the world (FAOSTAT, 2014). Jember Regency is the largest rice production center in East Java in 2016, but there are still many rice farmers who are less empowered. Based on these reasons, Jember Regency is one of the pilot projects of the upstream downstream agronomy program organized by East Java Province. This program aims to create farmer entrepreneurs who have added value, so that the concept of empowering farmers can be realized. The research approach uses a qualitative approach. The technique of determining informants used purposive sampling technique. Informants in this study included the department of food crops and horticulture in Jember Regency and a combination of farmer groups (Gapoktan Mitra Tani Sejati) in Candijati Village, Silo Jember District. The types of data used are primary data and secondary data. Data collection techniques using in-depth interviews, observation and literature. Data analysis techniques are carried out in three stages, namely data reduction, data presentation and conclusion drawing. The results and discussion show that the model of empowerment of rice farmers carried out by the local government of Kabupaten Jember in the upstream downstream program of agromarry in agriculture is a model of empowerment through partnerships. The empowerment model through partnership is an empowerment model that involves more than two or more stakeholders. The stakeholders include the East Java provincial government, the department of food crops and horticulture in Jember Regency, the Institute for Agricultural Technology Studies, under the Balitbangtan, the Indonesian Ministry of Agriculture, Bank Jatim as a fund buffer bank, insurance jasindo as guarantor, GAPOKTAN MITRA TANI SEJATI Sumber Jati Village Subdistrict Silo, and Farmers. All stakeholders have different functions and roles in making the upstream downstream agromaritime agriculture program successful. Until the evaluation of 2018, the upstream downstream agrarian program in agriculture has experienced problems in the process of scouring.